Synergistic protective effects of α-tocopherol and zinc sulfate on superoxide dismutase activity and p53 expression in ovarian granulosa cells of lead-exposed female Wistar rats (Rattus norvegicus) - iqbal dwi warsito; Suherni Susilowati; Erma Safitri; Ragil Angga Prastiya; Maya Nurwartanti Yunita; Amung Logam Saputro (Universitas Airlangga, 2025)
This study aimed to evaluate the protective effects of α-tocopherol and zinc sulfate on oxidative stress parameters in ovarian granulosa cells of female Wistar rats (Rattus norvegicus) exposed to lead acetate (Pb(C₂H₃O₂)₂). A total of 25 rats were randomly divided into five groups: Control (C), lead exposure only (T0), α-tocopherol + lead (T1), zinc sulfate + lead (T2), and α-tocopherol + zinc sulfate + lead (T3). Treatments were administered orally for 21 days. Superoxide dismutase (SOD) levels were measured spectrophotometrically, and p53 expression was analyzed using immunohistochemistry. The results showed that SOD levels significantly decreased in group T0 compared to the control (p <0.05), while treatment with either α-tocopherol (T1), zinc sulfate (T2), or their combination (T3) significantly improved SOD levels compared to T0. Moreover, p53 expression was markedly elevated in T0, indicating enhanced oxidative stress and potential apoptosis, whereas all antioxidant-treated groups showed reduced p53 expression, with T3 demonstrating values comparable to the control group. In conclusion, the combination of α-tocopherol and zinc sulfate provided a synergistic antioxidant effect, effectively enhancing SOD levels and suppressing p53 expression in granulosa cells of lead-exposed rats. This suggested a promising therapeutic potential of these compounds in mitigating lead-induced ovarian toxicity.